OPTIMIZATION OF FAMOTIDINE FLOATING TABLET FORMULA WITH COMBINATION OF HYDROXY PROPYL METHYL CELLULOSE K100M AND ETHYL CELLULOSE POLYMER - Veronica Vita Adyanti; Angi Nadya Bestari; T. N. Saifullah Sulaiman (Majalah Farmaseutik, 2016)
Famotidine is a gastric ulcer drug, which has a low bioavailability and a short half-life, therefore the dosage form that can maintain its existence in gastric is necessary to maximize its efficacy inhibiting H-2 receptor. Floating tablet can be an alternative because it can increase drug residence time in the gastric. This study aims to identify the combination effect of HPMC K100M and ethyl cellulose towards the physical characteristic of famotidine floating tablet and get an optimum ratio of both polymers. The formulas are made based on simplex lattice design method by using Design Expert® 10 software. Optimum formula is obtained by analyzing the parameters, which are significantly influenced by the difference of polymer concentration with numerical optimization and verified by IBM SPSS Statistics 19 software with one sample t-test method. Increased level of HPMC K100M gives a significant effect on increasing the medium absorption rate by granules and swelling index, decreasing dissolution rate, and accelerating floating lag time. Increased level of ethyl cellulose gives a significant effect on increasing flow rate of granules, tablet hardness, and drug release rate, decreased tap index of granules and tablet friability. The interaction of both polymers can improve swelling index and reduce the dissolution rate. The combination of HPMC K100M with 18,53% w/w concentration and ethyl cellulose with 16,47% w/w concentration can provide the optimum physical characteristic of famotidine floating tablet.